Ameliorating effect of Malva Neglecta on hyperglycemia and hyperlipidemia in diabetic rats (Brazilian Journal of Pharmaceutical Sciences, 2022)
The plant, Malva neglecta wallr., is widely consumed for medicinal and nutritional purposes. The current study was carried out to assess the hypoglycemic and antihyperlipidemic potential of aqueous methanolic extract of M. neglecta. Chemical evaluation of the extract was performed by high pressure liquid chromatography. Oral glucose tolerance test (OGTT) was done in diabetic rats pre-exposed to 250, 500 and 750 mg/kg plant extract via the oral route. For hypoglycemic and biochemical study, the same therapy was administered to alloxan induced diabetic rats for 14 days. The standard controlgroup received Glibenclamide (5 mg/kg). Ferulic acid, p-coumaric acid and other phenolic acids were detected and estimated in the extract. Administration of the plant extract significantly reduced blood glucose level in diabetic rats subjected to OGTT. The plant extract lowered the fasting blood glucose and alpha amylase, and prevented the damage to pancreas. It also corrected dyslipidemia in diabetic animals following 14 days therapy. Hence, this experimental study establishes the fact that M. neglecta exhibited significant antidiabetic and antihyperlipidemic activities in alloxan induceddiabetic rats.